Speaking materials for conversation class at Islamic senior high school - Mujawazah Mujawazah; Agus Widyantoro (LingTera, 2019)
This research study aimed to develop English speaking materials to support the learning process in Conversation class of the tenth-graders at Madrasah Aliyah (Islamic senior high school) Al Ma’had An Nur, Bantul. This research was a research and development study. The development was carried out through several steps, namely the needs analysis, a course grid design, product development, product validation, product revisions, try-outs, and final product development. The research had two results. First, it produced a set of speaking materials in the form of printed books. Second, the findings showed that the materials were appropriate to be applied in the Conversation class of the tenth-graders at Madrasah Aliyah Al Ma’had An Nur, Bantul considering the result of the materials evaluation by experts and students’ try-outs. They scored 3.59 and 3.32 for the mean score of the scale 1 to 4 and were categorized as “Very Good”.